Evaluation and driving factors of ecological integrity in the Alxa League from 1990 to 2020 - Sun, Haoyu; Cao, Weijia; Liu, Huan; Zhang, Xuefeng; Wang, Lixin; Wen, Lu (Frontiers in Ecology and Evolution, 2023)
Ecological integrity can satisfactorily reflect the comprehensive quality of ecosystems and has become a useful tool for evaluating the ecological environment. Ecological integrity evaluation has been widely applied in various ecosystems. Conducted in the Alxa League, the study established an ecological integrity index based on ecosystem structure, function and resilience and evaluated the ecological integrity of the study area in 1990, 2000, 2010 and 2020. Using hotspots spatial analyses, we analyzed the temporal and spatial variation of ecological integrity index during the study period. The main contributing factors affecting ecological integrity were identified with the help of the geographical detector model. Our results showed that (1) ecosystem structure, function and resilience in the Alxa League had obvious spatial heterogeneity and barely changed from 1990 to 2020. (2) Half of the area had a poor ecological integrity index, and the decrease in ecological integrity mainly occurred in the Alxa Left Banner.(3) Among the factors affecting the ecological integrity index, land use intensity was the major driving factor, and desertification was a key reason leading to the decrease. Ecological integrity evaluation can increase public awareness of desert conditions and guide policy makers to make reasonable and sustainable policies or strategies to protect and restore desert ecosystems.